The burden of injury in Brazil, 2003 - Gawryszewski, Vilma Pinheiro (2006)
CONTEXT AND OBJECTIVE: Since 1980, injuries have been the second biggest cause of death among the Brazilian population. This study aimed to analyze national data on fatal injuries and nonfatal injury hospitalization in Brazil, for 2003. DESIGN AND SETTING: This was a population- based descriptive study, Brazil, 2003. METHODS: Data from 126,520 fatal injuries and 733,712 nonfatal injuries seen at public hospitals were analyzed. The data were stratified by sex, age, intent and injury mechanism. Raw and age- and sex-specific rates were calculated per 100,000 individuals. RESULTS: The raw injury mortality rate was 71.5/100,000 (122.6/100,000 for male and 22.0/100,000 for female). For fatal injuries, the proportions of unintentional and intentional injuries were equal (44.3% and 46.9%, res- pectively). Homicides were the leading cause, 40.3% overall (28.8/100,000), followed by transport-related deaths, 26.2% overall (17.0/100,000). For nonfatal injuries, the rate was 414.8/100,000 and unintentional injuries were predominant (88.9%). Overall, the leading cause was unintentional falls, accounting for 42.6% of victims treated in public hospitals (176.8/100,000). Transport-related injuries were second: 15.0% overall; 62.0/100,000. Fractures comprised 46.7% of principal diagno- ses at hospitals. The injury types in the fatal and nonfatal datasets varied according to sex and age. The highest rates were found among young males and elderly people. CONCLUSIONS: Injury prevention activities need to be developed. To prevent deaths, homicide has to be addressed. Among hospitalized cases, falls are the most important problem. Traffic-related injuries play an important role in morbidity and mortality.